2020
DOI: 10.14744/phd.2020.89156
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Relationship Between Perceived Social Support Level and Healthy Lifestyle Behaviors

Abstract: Gebelikte algılanan sosyal destek düzeyi ile sağlıklı yaşam biçimi davranışları arasındaki ilişkinin incelenmesi K adın için gelişimsel bir kriz süreci olarak tanımlanan gebelik; kadın yaşamında fizyolojik, psikolojik ve sosyal uyumu gerektiren önemli bir süreç olarak tanımlanmaktadır. Gebeliğin sağlıklı sürdürülmesi ve sağlıklı bir şekilde sonlanmasında kadınların sağlık davranışları önemli bir yere sahiptir. [1,2] Bu nedenle intrauterin dönemde fetüsun fizyolojik, psikolojik, emosyonel ve spiritüel ihtiyaçla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Kanığ and Eroğlu concluded in their study that there is a positive relationship between the level of perceived social support in pregnancy and healthy lifestyle behaviors. It was determined that as the support of a particular person, family, and friends increased, the level of healthy lifestyle behaviors increased [22]. Similarly, Fathnezhad-Kazemi et al found that as the perceived social support score increased in pregnant women, the total score of health promotion behaviors increased [23].…”
Section: Discussionmentioning
confidence: 99%
“…Kanığ and Eroğlu concluded in their study that there is a positive relationship between the level of perceived social support in pregnancy and healthy lifestyle behaviors. It was determined that as the support of a particular person, family, and friends increased, the level of healthy lifestyle behaviors increased [22]. Similarly, Fathnezhad-Kazemi et al found that as the perceived social support score increased in pregnant women, the total score of health promotion behaviors increased [23].…”
Section: Discussionmentioning
confidence: 99%